Shapes of Apocalypse : Arts and Philosophy in Slavic Thought - Oppo, Andrea; Oppo, Andrea (Boston, MA Academic Studies Press)
This collective volume aims to highlight the philosophical and literary idea of apocalypse, within some key examples in the Slavic world during the nineteenth and twentieth century. From Russian realism to avant-garde painting, from the classic fiction of the nineteenth century to twentieth century philosophy, not omitting theatre, cinema or music, there is a specific examination of the concepts of end of history and end of present time as conditions for a redemptive image of the world. To understand this idea means to understand an essential part of Slavic culture, which; however divergent and variegated it may be in general, converges on a specific myth in a surprising manner.
English
Keywords: Arts; Art; Jerzy Grotowski; Miroslav Krleža; Nikolai Gogol